2016
DOI: 10.1073/pnas.1605769113
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms identified in Caenorhabditis elegans by in vivo long-term monitoring of a bioluminescent reporter

Abstract: Circadian rhythms are based on endogenous clocks that allow organisms to adjust their physiology and behavior by entrainment to the solar day and, in turn, to select the optimal times for most biological variables. Diverse model systems-including mice, flies, fungi, plants, and bacteria-have provided important insights into the mechanisms of circadian rhythmicity. However, the general principles that govern the circadian clock of Caenorhabditis elegans have remained largely elusive. Here we report robust molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 67 publications
0
55
0
Order By: Relevance
“…Casein kinase 1 (CK1) is a conserved component of circadian systems in eukaryotes and the pharmacological inhibition of CK1 affects the circadian period in mammals (Badura et al , 2007, Eide et al , 2005, Walton et al , 2009), Drosophila melanogaster (Meng et al , 2010), Neurospora crassa (Querfurth et al , 2011), Ostreococcus tauri (van Ooijen et al , 2013) and Caenorhabditis elegans (Goya et al , 2016). N. oceanica contains a CK1 gene with 72% identity with mouse casein kinase 1 ε (NannoCCMP1779|10930); this gene cycles under light/dark conditions with a peak at dawn (Figure S13a).…”
Section: Resultsmentioning
confidence: 99%
“…Casein kinase 1 (CK1) is a conserved component of circadian systems in eukaryotes and the pharmacological inhibition of CK1 affects the circadian period in mammals (Badura et al , 2007, Eide et al , 2005, Walton et al , 2009), Drosophila melanogaster (Meng et al , 2010), Neurospora crassa (Querfurth et al , 2011), Ostreococcus tauri (van Ooijen et al , 2013) and Caenorhabditis elegans (Goya et al , 2016). N. oceanica contains a CK1 gene with 72% identity with mouse casein kinase 1 ε (NannoCCMP1779|10930); this gene cycles under light/dark conditions with a peak at dawn (Figure S13a).…”
Section: Resultsmentioning
confidence: 99%
“…The study also demonstrated that light and temperature detection involve the use of photoreceptors GUR-3 and LITE, as well as TAX-2 cyclic nucleotide-gated channel subunit. Importantly, this bioluminescence assay is extremely sensitive, non-invasive and has immediate resolution (Goya et al, 2016). Therefore, C. elegans can be optimized to elucidate the molecular mechanisms behind the circadian patterns of RLS symptoms using those characterized behavioural and physiological activities controlled by circadian rhythms in C. elegans .…”
Section: Elegans Methods For Rls Studymentioning
confidence: 99%
“…Casein kinase 1 (CK1) is a conserved component of circadian systems in eukaryotes and the pharmacological inhibition of CK1 affects the circadian period in mammals (Eide et al, 2005;Badura et al, 2007;Walton et al, 2009), Drosophila melanogaster (Meng et al, 2010), Neurospora crassa (Querfurth et al, 2011), Ostreococcus tauri (van Ooijen et al, 2013) and Caenorhabditis elegans (Goya et al, 2016). Nannochloropsis oceanica contains a CK1 gene with 72% identity with mouse casein kinase 1 e (Nan-noCCMP1779|10930); this gene cycles under light/dark conditions with a peak at dawn ( Figure S13a).…”
Section: Potential Clock Components In the Nannochloropsis Genomesmentioning
confidence: 99%